PENGEMBANGAN FORMULA PERMEN JELLY RENDAH GULA DAN TINGGI ANTIOKSIDAN DARI EKSTRAK BUNGA ROSELLA (Hibiscus sabdariffa Linn.) - Zaddana, Cantika; Rusli, Zaldy; Wahyuningrum, Cyntia; Oktapiani, Ayu (Universitas Pakuan, 2024)
Rosella flowers contain anthocyanins which act as natural antioxidants and can ward off free radicals. One of the product innovations in the use of rosella flower petals is as a raw material for making jelly candy. The purpose of this study was to make a formula for jelly candy with rosella flower extract that met the quality requirements, determine the antioxidant activity and reducing sugar content of jelly candy with rosella flower extract, and determine the formula for jelly candy with rosella flower extract that the panelists liked the most. The test on the antioxidant activity test in this study used the DPPH method. Rosella flower extract was made in three formulas with concentrations of each formula F1 1%, F2 2%, and F3 3%. The results formula 1 obtained water content of 10.09%, ash content of 2.79%, metal contamination of Pb and Hg of 0.0034 mg/kg and 0.005 mg/kg, microbial contamination obtained was 5 colonies/g, and yeast mold contained 10 colonies/gram. Formula 2 obtained water content of 7.32%, ash content of 2.98%, metal contamination of Pb and Hg of 0.1 mg/kg and 0.005 mg/kg, no microbial contamination, and no yeast mold was obtained. Formula 3 obtained water content of 8.03%, ash content of 2.88%, metal contamination of Pb and Hg of 0.07 mg/kg and 0.005 mg/kg, no microbial contamination, and no yeast mold was obtained. The formula that has the best antioxidant activity and is low in sugar is formula 3 which has the potential for free radical inhibition of 39.10 ppm (strong activity) or equivalent to the consumption of 0.391 mg of jelly candy and has a reducing sugar content of 15.20. The rosella flower extract jelly candy formula that was more favored by the panelists was formula 1 based on the parameter values of taste, color and texture.